On certain classes of limit distributions - Mišeikis, F. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Ф. Мишейкис. О некоторых классах предельных распределенийF. Mišeikis. Apie kai kurias ribinių pasiskirstymų klases